Smart urbanism and smart citizenship: The neoliberal logic of 'citizen-focused' smart cities in Europe. (August 2019) - Cardullo, Paolo; Kitchin, Rob
This paper examines the neoliberal ideals that underpin participation and citizenship in the smart city and their replication mechanisms at the European level, particularly focusing on the work of the European Innovation Partnership for Smart Cities and Communities. The research consisted of three levels of data generation and analysis: a discourse analysis of policy documents and project descriptions of the 61 Commitments in the European Innovation Partnership for Smart Cities and Communities 'citizen-focus' cluster; interviews with a dozen stakeholders working on citizen engagement in a small sample of European Innovation Partnership for Smart Cities and Communities flagship projects; and twenty interviews with city officers and corporate exhibitors at the 2017 Smart City Expo and World Congress. We contend that smart cities as currently conceived enact a blueprint of neoliberal urbanism and promote a form of neoliberal citizenship. Supra-national institutions like the European Innovation Partnership for Smart Cities and Communities act at a multi-scalar level, connecting diverse forms of neoliberal urbanism whilst promoting policy agendas and projects that perform neoliberal citizenship in the spaces of the everyday. Despite attempts to recast the smart city as 'citizen-focused', smart urbanism remains rooted in pragmatic, instrumental and paternalistic discourses and practices rather than those of social rights, political citizenship, and the common good. In our view, if smart cities are to become truly 'citizen-focused', an alternative conception of smart citizenship needs to be deployed, one that enables an effective shift of power and is rooted in the right to the city, entitlements, community, participation, commons, and ideals beyond the market.